Chapter Mainland Southeast Asian languages: State of the art and new directions. - Enfield, N.J (De Gruyter, 2015)
Mainland Southeast Asia (hereafter: MSEA) can be broadly defined as the area occupied by present day Cambodia, Laos, Peninsular Malaysia, Thailand, Myanmar, and Vietnam, along with areas of China south of the Yangtze River. Also sometimes included are the seven states of Northeast India, and-although here the term 'mainland' no longer applies-the islands from Indonesia and Malaysia running southeast to Australia and West Papua (see Map 1). There are no exact borders around the MSEA area. Different scholars draw lines in different places. But there is nevertheless a core (Comrie 2007: 45). MSEA is always taken to include Indochina-Vietnam, Laos, and Cambodia-together with Thailand, and, usually, Peninsular Malaysia and part or all of Myanmar (see Map 2). This book covers the broader scope of Greater MSEA, with several chapters moving beyond the core area of Indochina and Thailand, in all directions; see chapters in this book by Vittrant and by Jenny on Myanmar (cf. Bradley 1995; Watkins 2005), by Post on Northeast India (cf. Morey and Post 2008, 2010; Hyslop, Morey, and Post 2011, 2012, 2013), by Gil on Insular Southeast Asia (cf. Adelaar and Himmelmann 2005; Blust 2013a, b), and by de Sousa on Southern China (cf. Bauer 1996; Ansaldo and Matthews 2001; Chappell 2001).